Acute Renal Insufficiency: Current Knowledge - Baptista, Alexandre; Silva, Ana; Neves, Pedro (Portuguese Journal Internal Medicine, 2008)
Acute Renal Failure (ARF) is a common problem for most doctors, whether dealing with out-patients or in-patients. Although there is a better knowledge of physiopathology and there are new drugs available for prophylaxis and treatment, the mortality rate for ARF continues to be high. This review summarizes our present knowledge of ARF and deals with the latest advances in this area.